2007
DOI: 10.1007/s12072-007-9016-3
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir for the treatment of lamivudine-refractory chronic hepatitis B patients in China

Abstract: Purpose This randomized, double-blind, placebo-controlled study was undertaken to evaluate the efficacy and safety of entecavir in Chinese patients with lamivudinerefractory chronic hepatitis B.Methods One hundred forty-five lamivudine-refractory patients with chronic hepatitis B were randomized to double-blind treatment with oral entecavir 1 mg (n = 116) or placebo (n = 29) daily for 12 weeks, followed by 36 weeks of open-label entecavir treatment. The primary efficacy endpoint was the mean change from baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
6
4
1
Order By: Relevance
“…The week 48 virologic results with ETV monotherapy were consistent with those described previously for ETV in LAMrefractory or LAM-resistant populations; 30,[39][40][41][42] efficacy data from the second year are of limited value, as they reflect a mixed treatment strategy, with 33 patients adding TDF after week 48.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The week 48 virologic results with ETV monotherapy were consistent with those described previously for ETV in LAMrefractory or LAM-resistant populations; 30,[39][40][41][42] efficacy data from the second year are of limited value, as they reflect a mixed treatment strategy, with 33 patients adding TDF after week 48.…”
Section: Discussionsupporting
confidence: 83%
“…In all three arms, serologic response rates were low (HBeAg seroconversion rates < 10%), a finding which has been reported previously in LAM-experienced patients receiving rescue therapy, 30,[40][41][42] and which may be due to extensive prior treatment selecting for HBeAg(+) patients with an inherent barrier to seroconversion. Furthermore, over 80% of the patients had HBV genotype C infection, which has been associated with a lower probability of achieving a serologic response.…”
Section: Discussionsupporting
confidence: 68%
“…Phase II and III studies in the more difficult-to-treat lamivudine-refractory population were completed in multinational12,18 and Asian cohorts 19,20. Week 48 HBV DNA suppression was not as robust as seen in naïve patients, with mean decreases of about 5 log copies/mL.…”
Section: Clinical Studies Of Efficacymentioning
confidence: 99%
“…11 Therapy with ETV resulted in superior histological, biochemical, and virological efficacy after 1 year of treatment compared with lamivudine in HBeAg-positive and HBeAg-negative patients with CHB. [12][13][14][15][16] Follow-up of patients treated in clinical trials beyond 48 weeks demonstrated durable viral suppression. [17][18][19][20] Viral kinetic studies of nucleoside analogs have shown a biphasic decay in HBV DNA.…”
mentioning
confidence: 99%